Socialization of Non-Cash Payment for Health Services Using the Indonesian Standard Quick Response Code (QRIS) at Langsa Hospital - Afnina Afnina; Erni Junaida; Nada Salsabila; Nurlaila Hanum; Nurhayati Ningsih (CV. Rayyan Dwi Bharata, 2023)
Langsa Hospital's efforts to welcome the central government's program regarding digital-based payments have been implemented since September 21, 2021. It's just that until now non-cash payment for health services using QRIS at Langsa Hospital is still low. The community service team saw this problem and conducted socialization by collaborating with the first partner, Langsa Hospital and the second partner, the Langsa branch of YAI, to socialize non-cash payment of health services using QRIS at Langsa Hospital, which was attended by 850 participants. The methods used are lectures, questions and answers, practice of using QRIS. So based on the results of this socialization it was found that only 27 participants (3.18%) had used QRIS at Langsa Hospital and the remaining 823 participants (96.82%) had not. The participants looked enthusiastic and enthusiastic about participating in the event until the end and with additional information from the resource persons and the team, the participants were interested in using QRIS if they went to a hospital for treatment.